Lumbar Scoliosis Combined Lumbar Spinal Stenosis and Herniation Diagnosed Patient Was Treated with "U" Route Transforaminal Percutaneous Endoscopic Lumbar Discectomy. (19th January 2017) - Wu, Binbin; Zhang, Shaobo; Lian, Qingquan; Yan, Haibo; Lin, Xianfa; Zhan, Gonghao
Abstract : The objective was to report a case of a 63-year-old man with a history of low back pain (LBP) and left leg pain for 2 years, and the symptom became more serious in the past 5 months. The patient was diagnosed with lumbar scoliosis combined with lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH) at the level of L4-5 that was confirmed using Computerized Topography and Magnetic Resonance Imaging. The surgical team preformed a novel technique, "U" route transforaminal percutaneous endoscopic lumbar discectomy (PELD), which led to substantial, long-term success in reduction of pain intensity and disability. After removing the osteophyte mass posterior to the thecal sac at L4-5, the working channel direction was changed to the gap between posterior longitudinal ligament and thecal sac, and we also removed the herniation and osteophyte at L3-4 with "U" route PELD. The patient's symptoms were improved immediately after the surgical intervention; low back pain intensity decreased from preoperative 9 to postoperative 2 on a visual analog scale (VAS) recorded at 1 month postoperatively. The success of the intervention suggests that "U" route PELD may be a feasible alternative to treat lumbar scoliosis with LSS and LDH patients.